Computed Tomography Overuse in Pediatric Minor Head Trauma: Insights from a Single-Center Experience - Bako, Derya; Özer, Utku; Beydoğan, Engin (Klinische Pädiatrie, 2023)
Background Minor head trauma is a common reason for emergency department visits in children, but many of these cases are not clinically significant. Despite established criteria for selecting patients who require computed tomography (CT), concerns about overuse of CT persist. This study aimed to determine the frequency of clinically important traumatic brain injury by retrospectively evaluating cranial CT scans in children categorized as very low risk for such injuries based on PECARN prediction rules.Materials and Methods Cranial CT scans of 941 minor head trauma cases were assessed for the presence, type, and number of calvarial bone fractures. Concomitant bleeding and treatment approaches were also recorded.Results Among 881 patients (93.6%), cranial CT scans did not reveal any lesions apart from soft tissue edema. None of the cases had clinically important traumatic brain injury or required neurosurgical intervention.Discussion and conclusion The study demonstrated that 93.6% of cranial CT scans for pediatric minor head trauma were negative, indicating a concerningly high rate of CT overuse. Although prediction rules exist, their application in clinical practice is not always optimal. Given the principle of “first, do no harm,” proper patient selection is crucial to avoid unnecessary exposure to ionizing radiation.
Keywords: computed tomography; children; minor head trauma; overuse